2009
DOI: 10.1007/s00432-009-0605-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of p53, MDM2 and p14ARF protein expression in human esophageal squamous cell carcinoma

Abstract: Expression of p53 protein correlates with increased MDM2 and p14(ARF) protein levels in ESCC. In addition, status of p53 (wild-type versus mutant) rather than expression level of p53, MDM2, or p14(ARF) is likely to be the more critical determinant of clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…This is the first time we showed that there is a possibility in cooperation between MT1-MMP and p14ARF in cancer development in HSC5 cells. In the other hand, our results showed that 3 µM arsenic induced apoptosis of HSC5 cells via downregulation of N-cadherin (Figure 4A), which plays role in cell differentiation, transformation, as well as invasion [33][36] and upregulation p21(WAF1/CIP1) (Figure 4B), a tumor suppressor [20][24] at both transcript and expression levels. Our results in accordance with previous studies [37], [38] suggested that N-cadherin might participate to the associated-cell cycle arrest through the nuclear accumulation of cyclin-dependent kinase inhibitors p21.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…This is the first time we showed that there is a possibility in cooperation between MT1-MMP and p14ARF in cancer development in HSC5 cells. In the other hand, our results showed that 3 µM arsenic induced apoptosis of HSC5 cells via downregulation of N-cadherin (Figure 4A), which plays role in cell differentiation, transformation, as well as invasion [33][36] and upregulation p21(WAF1/CIP1) (Figure 4B), a tumor suppressor [20][24] at both transcript and expression levels. Our results in accordance with previous studies [37], [38] suggested that N-cadherin might participate to the associated-cell cycle arrest through the nuclear accumulation of cyclin-dependent kinase inhibitors p21.…”
Section: Discussionmentioning
confidence: 86%
“…Treatment with 3 µM of arsenic induced transcript and expression levels of MT1-MMP (Figure 3A-B) and inhibited transcript and expression levels of p14ARF (Figure 3C-D). Previous studies [20][24], [27] indicated that MT1-MMP and p14ARF might play important roles in modulating growth and invasion of squamous cell carcinoma cells. In accordance with these previous reports [20][24], [27], our results suggested that arsenic might promote invasion of HSC5 cells via upregulation of MT1-MMP and downregulation of p14ARF.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations